The South-Carolina almanack and register, for the year of our Lord 1762 ... Calculated for the latitude of 32 deg. 40 min. north, and longitude 78 deg. 45 min. west from London; and may serve, without any sensible errour, for any part of South-Carolina, Georgia, or North-Carolina ... / By George Andrews, Esq. ; [One line of quotation in Latin] [microform] : (1761)
Summary goes here